2022
DOI: 10.3390/cancers14153712
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Nucleic Acids in the Diagnosis and Progression of Colorectal Cancer

Abstract: Colorectal cancer (CRC) is the 3rd most common malignant neoplasm worldwide, with more than two million new cases diagnosed yearly. Despite increasing efforts in screening, many cases are still diagnosed at a late stage, when mortality is high. This paper briefly reviews known genetic causes of CRC (distinguishing between sporadic and familial forms) and discusses potential and confirmed nucleic acid biomarkers obtainable from liquid biopsies, classified by their molecular features, focusing on clinical releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 174 publications
(122 reference statements)
1
4
0
Order By: Relevance
“…A total of 127 downregulated genes and 114 upregulated genes were identified by using GEO2R to detect DEGs in colorectal cancer tissue samples versus normal tissue samples. These DEGs were shown to be mainly involved in GO enrichment analysis of cellular response to chemical stimulus, extracellular region, carbonate dehydratase activity, cell division, spindle, cell adhesion molecule binding, Aldosterone-regulated sodium reabsorption for KEGG pathway analysis, Cell cycle, etc, and is in line with our knowledge, [21] such as Jakub Styk et al [22] found that the presence of free nucleic acids in the cycle (cfNAs) present in the circulation are bound to protein complexes or encapsulated in extracellular membrane vesicles (e.g., apoptotic vesicles, microvesicles, or exosomes), which mediate intercellular communication and thus play an important role in Figure 2. Interaction network and biological process analysis of the hub genes.…”
Section: Discussionsupporting
confidence: 73%
“…A total of 127 downregulated genes and 114 upregulated genes were identified by using GEO2R to detect DEGs in colorectal cancer tissue samples versus normal tissue samples. These DEGs were shown to be mainly involved in GO enrichment analysis of cellular response to chemical stimulus, extracellular region, carbonate dehydratase activity, cell division, spindle, cell adhesion molecule binding, Aldosterone-regulated sodium reabsorption for KEGG pathway analysis, Cell cycle, etc, and is in line with our knowledge, [21] such as Jakub Styk et al [22] found that the presence of free nucleic acids in the cycle (cfNAs) present in the circulation are bound to protein complexes or encapsulated in extracellular membrane vesicles (e.g., apoptotic vesicles, microvesicles, or exosomes), which mediate intercellular communication and thus play an important role in Figure 2. Interaction network and biological process analysis of the hub genes.…”
Section: Discussionsupporting
confidence: 73%
“…Yet, robust evidence is still lacking. This Special Issue further contributes to this growing body of data, showing that cfDNA methylation signatures hold promise for identifying precancerous lesions and early-stage tumors for hepatocellular carcinoma and colorectal cancer [4][5][6][7]. Beyond early detection, cfDNA has shown its utility as a predictive biomarker for certain tumors, enabling clinicians to tailor treatment strategies to individual patients based on their unique genomic profiles.…”
mentioning
confidence: 88%
“…Over the past decade, much effort has been devoted to the development of non-invasive approaches for cancer diagnosis and monitoring to replace the conventional invasive techniques [ 129 , 130 , 131 ]. Although associations between TL and cancer risk or prognosis have been extensively investigated in tumor tissues [ 69 ], cell-free telomeric DNA (cf-telDNA) remains poorly explored despite its potential suitability to become an informative genetic biomarker for many cancers ( Table 2 ).…”
Section: Applications Of Telomeric Dna In Cancer Assessmentmentioning
confidence: 99%